Enantioselective Rhodium-Catalyzed Cycloisomerization of 1,6-Allenynes to access 5/6-Fused Bicycle[4.3.0]nonadienes - Deng, Xu; Shi, Li-Yang; Lan, Jialing; Guan, Yu-Qing; Zhang, Xiaoyong; Lv, Hui; Chung, Lung Wa; Zhang, Xumu (Nature communications, 2019)
Transition-metal-catalyzed cycloisomerization of 1,n-allenynes represents a powerful synthetic tool to rapidly assemble complex polycyclic skeletons from simple linear substrates. Nevertheless, there are no reports of the asymmetric version of these reactions. Moreover, most of these reactions proceed through a 6-endo-dig cyclization pathway, which preferentially delivers the distal product (via 5/5 rhodacyclic intermediate) rather than the proximal one (via 6/5 rhodacyclic intermediate). Herein, we report an enantioselective rhodium(I)-catalyzed cycloisomerization of 1,6-allenynes to provide the proximal product 5/6-fused bicycle[4.3.0]nonadienes in good yields and with excellent enantioselectivities. Remarkably, this chemistry works perfectly for 1,6-allenynes having a cyclic substituent within the allene component, thereby affording synthetically formidable tricyclic products with excellent enantioselectivities. Moreover, extensive DFT calculations suggest an uncommon pathway involving 5- exo - dig cycloisomerization, ring-expansion, rate-determining alkene isomerization involving C sp3 -H activation, C-C activation of the cyclobutene moiety and finally reductive elimination. Deuterium labeling experiments support the rate-determining step involving the C–H bond activation in this transformation. Cycloisomerization of 1,n-allenynes allows to efficiently assembly polycyclic skeletons, however its asymmetric variant remains elusive. Here, the authors report the enantioselective Rh(I)-catalyzed cycloisomerization of 1,6-allenynes and disclose an uncommon 5-exo-dig pathway via DFT calculations.